2020
DOI: 10.12984/egeefd.588512
|View full text |Cite
|
Sign up to set email alerts
|

Oyunlaştırılmış Robot Etkinliklerinin Ortaokul Öğrencilerinin Problem Çözme ve Bilgi İşlemsel Düşünme Becerilerine Etkisi

Abstract: Bu araştırmanın amacı, oyunlaştırılmış eğitsel robot etkinliklerinin, ortaokul öğrencilerinin problem çözmeye yönelik yansıtıcı düşünme becerilerine ve bilgi işlemsel düşünme beceri düzeylerine etkisini belirlemektir. Araştırmada öntest sontest kontrol gruplu yarı deneysel desen kullanılmıştır. Araştırmanın deney grubunu, 2018-2019 Eğitim-Öğretim Yılı'nda Bilişim Teknolojileri ve Yazılım Dersi 2. Dönem Destekleme ve Yetiştirme Kursuna kayıtlı 27 kişiden oluşan 6. sınıf öğrencileri oluşturmaktadır. Kontrol grub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…On the other hand, students who have a protective family and have difficulties in interpersonal relationships had a higher professional anxiety level can be explained by the fact that students with such characteristics have difficulties in adapting to the external environment and life, exhibit an insecure attitude towards the individuals around them, and this situation has a negative reflection on the level of general anxiety. 21 Also, considering that the thought of facing unemployment after undergraduate students' graduation is an important cause of anxiety, the fact that the professional anxiety level of first-grade students were low, while the level of second, third, and fourth-grade students were high, suggested that this situation is related to future anxiety. 15,22 Lastly, the lower professional anxiety level of students with higher average income and higher perceived socio-economic level can be explained by the fact that they are aware of the financial support to be provided by their families in any unfavorable condition and this situation creates comfort and confidence in students.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, students who have a protective family and have difficulties in interpersonal relationships had a higher professional anxiety level can be explained by the fact that students with such characteristics have difficulties in adapting to the external environment and life, exhibit an insecure attitude towards the individuals around them, and this situation has a negative reflection on the level of general anxiety. 21 Also, considering that the thought of facing unemployment after undergraduate students' graduation is an important cause of anxiety, the fact that the professional anxiety level of first-grade students were low, while the level of second, third, and fourth-grade students were high, suggested that this situation is related to future anxiety. 15,22 Lastly, the lower professional anxiety level of students with higher average income and higher perceived socio-economic level can be explained by the fact that they are aware of the financial support to be provided by their families in any unfavorable condition and this situation creates comfort and confidence in students.…”
Section: Discussionmentioning
confidence: 99%
“…Karaahmetoğlu (2019) found that activities based on educational robots are more effective in increasing students' computational thinking skills than block-based programming activities. Similarly, Kaya, Korkmaz & Çakır (2020) stated in their research that gamified robotic educational activities increase students' computational thinking skills.…”
Section: Methodsmentioning
confidence: 98%
“…Upon reviewing the studies in the literature, it is seen that coding education contributes positively to students' CT skills (Erümit et al, 2020;Kaya et al, 2020;Pérez-Marín et al, 2020;Oluk et al, 2018;Zhaou & Shute, 2019). Nevertheless, to heighten the validity of studies in the literature, more research employing experimental designs is needed on teaching CT skills through coding (Ataman-Uslu et al, 2018;Zhang & Nouri, 2019).…”
Section: Plugged and Unplugged Coding For Computational Thinkingmentioning
confidence: 99%
“…Nevertheless, to heighten the validity of studies in the literature, more research employing experimental designs is needed on teaching CT skills through coding (Ataman-Uslu et al, 2018;Zhang & Nouri, 2019). In addition, different coding activities and different methods were used in different studies (Erümit et al, 2020;Kaya, et al, 2020;del Olmo-Muñoz et al, 2020). It is necessary to compare how different programming languages and tools improve CT skills (Zhang & Nouri, 2019).…”
Section: Plugged and Unplugged Coding For Computational Thinkingmentioning
confidence: 99%